2004
DOI: 10.1038/sj.bjp.0705698
|View full text |Cite
|
Sign up to set email alerts
|

Endothelium‐dependent smooth muscle hyperpolarization: do gap junctions provide a unifying hypothesis?

Abstract: An endothelium‐derived hyperpolarizing factor (EDHF) that is distinct from nitric oxide (NO) and prostanoids has been widely hypothesized to hyperpolarize and relax vascular smooth muscle following stimulation of the endothelium by agonists. Candidates as diverse as K+ ions, eicosanoids, hydrogen peroxide and C‐type natriuretic peptide have been implicated as the putative mediator, but none has emerged as a ‘universal EDHF’. An alternative explanation for the EDHF phenomenon is that direct intercellular commun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
240
0
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 216 publications
(250 citation statements)
references
References 284 publications
(501 reference statements)
5
240
0
5
Order By: Relevance
“…Tetraethylamonium chloride is an inhibitor of the endothelial calcium-sensitive potassium channels, whose inhibition induces relaxation through the hyperpolarization of vascular smooth muscle membrane. 26 In support of the hypothesis that midazolam induces hyperpolarization, suggested by Klockgether-Radke et al, 11 we found that the vasodilation resulting from the low dose, or 'endothelial dose,' of midazolam in KCl-precontracted rings was lower than the vasodilation observed in phenylephrine-precontracted rings ( Figures 1a and b). Depolarization of the vascular smooth muscle cells of aortic rings induced by the high concentration of KCl in the bath (80 mmol l À1 ) may overwhelm the hyperpolarization induced by the 'endothelial dose' of midazolam.…”
Section: Discussionsupporting
confidence: 85%
“…Tetraethylamonium chloride is an inhibitor of the endothelial calcium-sensitive potassium channels, whose inhibition induces relaxation through the hyperpolarization of vascular smooth muscle membrane. 26 In support of the hypothesis that midazolam induces hyperpolarization, suggested by Klockgether-Radke et al, 11 we found that the vasodilation resulting from the low dose, or 'endothelial dose,' of midazolam in KCl-precontracted rings was lower than the vasodilation observed in phenylephrine-precontracted rings ( Figures 1a and b). Depolarization of the vascular smooth muscle cells of aortic rings induced by the high concentration of KCl in the bath (80 mmol l À1 ) may overwhelm the hyperpolarization induced by the 'endothelial dose' of midazolam.…”
Section: Discussionsupporting
confidence: 85%
“…There is substantial support for the concept that EDHF, rather than being a 'factor' per se, might simply represent the transfer of hyperpolarizing current from the endothelial cell to the smooth muscle, a phenomenon facilitated by the myoendothelial gap junction (Griffith 2004). This thesis is supported by several studies using blockers of gap junctional communication that have demonstrated selective inhibition of vasodilator responses attributable to EDHF (Griffith 2004). These junctional structures are formed by intracellular channels that are composed of different members of the connexin (Cx) protein family (Griffith 2004).…”
Section: Edhfmentioning
confidence: 99%
“…Perhaps the most-described phenomenon relating to estrogen-induced changes in endothelial activity is the impact these hormones have on vascular tone mediated via stimulation of the release of endothelium-derived vasodilators. The most significant vasodilator factors that the endothelium releases are prostacyclin (PGI 2 ; Moncada et al 1976), nitric oxide (NO; Ignarro et al 1987, Palmer et al 1987, Furchgott & Vanhoutte 1989, Moncada & Higgs 2006, and endothelium-derived hyperpolarizing factor (EDHF; Chen et al 1988, Griffith 2004, Ahluwalia & Hobbs 2005. The biological activity and functions of endothelium-derived NO and PGI 2 in the cardiovascular system are well established and include not only vasodilatation but also inhibition of platelet aggregation, leukocyte recruitment, and smooth muscle growth (Moncada & Vane 1981, Moncada & Higgs 1991.…”
Section: Introductionmentioning
confidence: 99%
“…EDHF activity is blocked by high extracellular K ϩ concentration ([K ϩ ] o ) and K ϩ channel blockers, which prevent cells from being hyperpolarized. The chemical identity of EDHFs has received considerable attention; however, the existence and mechanism of action of EDHFs varies in different vascular beds, sizes, species, aging, and disease (4,5,21,44,50). Potassium ion, arachidonic acid (AA) metabolites, residual NO, H 2 O 2 , C-type natriuretic peptide, and myoendothelial cell gap junction are major EDHF candidates (5-7, 9, 12, 14, 21, 27, 44).…”
mentioning
confidence: 99%